Studi Tentang Dampak Struktur dan Perputaran Modal Kerja terhadap Profitabilitas pada Perusahaan Sektor Makanan dan Minuman Tercatat di Bursa Efek Indonesia - Tedi, Edi; Dwiyono, Gatot; Ruyani, Nur Ahmad; Setiawan, Kartiwan (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
Profitability reflects a company's ability to generate profits and indicates the effectiveness of its management. This is demonstrated by the profits generated from sales and investment income, which are utilized to finance the company's daily operations, as well as for investments and other purposes. The amount of capital required by a company depends on the magnitude of the expenses it incurs. There are numerous factors that can influence profitability, and this research focuses on two factors: capital structure and working capital turnover. The methodology employed in this study is a descriptive and verification method with a quantitative approach. The population consists of annual financial data from 14 companies in the food and beverages sector listed on the Indonesia Stock Exchange, with a sample size of 6 companies selected for analysis. The findings indicate that the capital structure, working capital turnover, and profitability fluctuate annually. Additionally, the statistical analysis reveals that both the capital structure and working capital turnover have a significant simultaneous effect on firm value. However, when examined individually, the capital structure does not significantly affect profitability, whereas the turnover of working capital exhibits a partial significant effect on profitability.